Analisis Pengaruh Motivasi Kerja, Disiplin Kerja Kepemimpinan Partisipatif, dan Budaya Organisasi Terhadap Kinerja Anggota Kepolisian Resort Alor - Alvonso Fanisius Gorang; Theresia L. L. Peny; Sefnat Aristarkus Tang; Hermayanti Hermayanti (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to determine whether there is an effect of Work Motivation, Work Discipline, Participatory Leadership, and Organizational Culture on Performance. The research was conducted on 334 members of the Alor Resort Police. Based on the results of the study, the results of simple linear regression showed that. Partially, work motivation has a significant value of 0.025, this value is smaller than the alpha value of 0.05, thus there is a significant effect of the motivation variable on performance. Partially, work discipline has a significant value of 0.004 where this value is smaller than the alpha value of 0.05, thus there is a significant effect of the work discipline variable on performance. Partially participatory leadership has a significant value of 0.018 where this value is smaller than the alpha value of 0.05, thus there is a significant influence of the participatory leadership variable. Partially organizational culture has a significant value of 0.039, where this value is smaller than the alpha value of 0.05, thus there is a significant influence of organizational culture variables on performance. Simultaneously the variables of work motivation, work discipline, participatory leadership, and organizational culture have a significant value of 0.000 where this value is smaller than the alpha value of 0.05 so that the variables of work motivation, work discipline, participatory leadership, and organizational culture have a significant effect on performance